(untitled) (Journal of Engineering, 2024)
Today’s world is witnessing continuous development, particularly in the construction sector, which is meeting the rising population and their need for essential facilities; this is one of the reasons why construction is witnessing such development. Different crises significantly affect this sector, including the financial crisis in different countries. This paper identifies the financial crises, their categories, and the reasons for appearing them. Inflation, currency exchange fluctuations, and the drop in global oil prices are the most important reasons for the emergence of external financial crises, especially in Iraq, which considers oil an important economic resource for its budget. The unexpected global financial events led to an economic collapse that affected the construction sector. Many large projects in Iraq have been put on hold as a result of these conditions due to the country’s lack of resources to address these crises. This paper aims to study and identify potential crises and potential responses and mitigation strategies for each crisis stage.